2003
DOI: 10.1074/jbc.m211204200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lytic Peptide Composed of dl-Amino Acids Selectively Kills Cancer Cells in Culture and in Mice

Abstract: The high toxicity of most chemotherapeutic drugs and their inactivation by multidrug resistance phenotypes motivated extensive search for drugs with new modes of action. We designed a short cationic diastereomeric peptide composed of D-and L-leucines, lysines, and arginines that has selective toxicity toward cancer cells and significantly inhibits lung metastasis formation in mice (86%) with no detectable side effects. Its ability to depolarize the transmembrane potential of cancer cells at the same rate (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 24 publications
5
113
0
1
Order By: Relevance
“…This binding is governed mainly by electrostatic interactions (45). Membrane binding forces the peptide to adopt a functional structure, which allows destabilization of the membrane (31). In agreement with this, many cancer cells have approximately (46)] they create the additional negative charge.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…This binding is governed mainly by electrostatic interactions (45). Membrane binding forces the peptide to adopt a functional structure, which allows destabilization of the membrane (31). In agreement with this, many cancer cells have approximately (46)] they create the additional negative charge.…”
Section: Discussionmentioning
confidence: 70%
“…A plausible explanation for this selective activity could be as follows: A common feature found in amphipathic-L and all of the other noncellselective peptides is their stable amphipathic ␣-helical structure in membranes as well as their similar affinity to negatively charged and zwitterionic membranes. Structural studies revealed that both amphipathic-L and amphipathic-D have unordered structures in solution (31). However, whereas amphipathic-L strongly binds and becomes fully helical in any type of membrane, amphipathic-D binds ϳ15-fold better negatively charged membranes compared with zwitterionic membranes (45).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations